Methods for Planning Effective Linkages - Peterson, Warren; Galleno, V.; Eponou, Thomas; Wuyts-Fivawo, Anna (International Service for National Agricultural Research, 2001)
Linkages between major institutional actors in agricultural knowledge and information systems (AKIS) are widely recognized as essential for an effective flow of technology and information between research, extension, and farmers. Poor performance of the system is often related to common and recurrent linkage problems among these actors and other stakeholders. Based on lessons learned through the collaborative application in four countries of a linkage planning approach developed by ISNAR, tested methods for improving linkages are summarized in this briefing paper.